Pengembangan Lingkungan Belajar Ramah Anak di Kecamatan Manyar melalui Pemberdayaan Komunitas dan Pelatihan Edukatif - Hasanah, Muhimmatul; Zunaih, Ahmad Iwan (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This community engagement program aims to enhance the understanding and capacity of teachers and parents in developing a child-friendly learning environment in Manyar District, Gresik. The main issue addressed is the lack of knowledge regarding Child-Friendly School (CFS) principles and the persistence of non-humanistic educational practices. A participatory seminar method was employed, combining educational and reflective approaches across three key sessions: material delivery, case discussions, and the development of school-based action plans. The results indicated a significant increase in participants’ understanding, with post-test scores improving by 37.4% compared to pre-tests. Furthermore, 86.7% of participants developed follow-up action plans, and two partner schools implemented safe zones and children’s expression corners in classrooms. This program demonstrates that collaborative educational strategies are effective in promoting school ecosystems that respect children’s rights and support their holistic development.